Protecting and Securing Sensitive Data in a Big Data Using Encryption - S. Banasode, Praveen; Padmannavar, Sunita (EAI Endorsed Transactions on Smart Cities, 2020)
The Transaction data which contains a sensitive data, a program like a android app or a browser, does not adequately protect information such as unique values or related payment information, more or likely a privacy concern. In most of the cases, security breaches, which involve the unstructured data like documents and files, will reveal all sensitive information. To address this issue the transaction data can be processed across the nodes based on Advanced Encryption Standard(AES) algorithm for generating keys and also by using MapReduce algorithm to check number of sensitive data, where we will partition the data based on set key value pairs, whereby protecting the raw data using real-time security monitoring. The data, which requires an extra protection, needs to be identified, based on that data can be encrypted.
Keywords: Advanced Encryption Standard (AES); real-time security monitoring; sensitive data